Educational Psychologists as 'Dissenting Voices': Thinking Again about Educational Psychologists and Social Justice - Daniela Mercieca; Duncan P. Mercieca (MDPI AG, 2022)
This paper locates the educational psychologist's (EP) involvement in addressing social justice in practice. It uses some philosophical ideas from Jacques Rancière, particularly the idea of the distribution of the sensible and dissensus, to help us question how systems that are aimed at contributing to a socially just society can limit social justice itself. Whilst the argument of this paper is applicable to educational psychologists internationally, this paper is situated within a Scottish context. It uses a vignette to draw out a philosophical reading of the EP's involvement in the narrative. This paper gives some examples of how structures that are aimed at supporting social justice often position the EPs within these systems so that thinking, being and doing are shaped according to the structures that they inhabit. The establishment of such structures and discourses have limited the meaning and implementation of social justice. This means that the identity of both those requiring the involvement of the EP, as well as the EP and other professionals is determined in terms of their 'proper place' and their activity is determined in terms of its 'proper function'. The paper argues that EPs can interrupt the procedural flow and provide a dissenting voice which can ultimately lead to social justice in ways that the normal flow of procedure does not.